Techno-economic and environmental assessment of bioethanol production from high starch and root yield Sri Kanji 1 cassava in Malaysia - M. Hanif; T. M. I. Mahlia; H. B. Aditiya; W. T. Chong; Nasruddin (Energy Reports, 2016)
Transportation played a significant role in energy consumption and pollution subsequently. Caused by the intense growth of greenhouse gas emission, efficient and sustainable improvement of the transportation sector has elevated the concern in many nations including Malaysia. Bioethanol is an alternative and renewable energy that has a great potential to substitute for fossil gasoline in internal combustion engine (ICE). Although bioethanol has been widely utilized in road transport worldwide, the production and application of bioethanol in Malaysia is yet to be considered. Presently there is comprehensive diversity of bioethanol research on distillation, performance and emission analysis available worldwide. Yet, the study on techno-economic and feasibility of bioethanol fuel in Malaysia condition is unavailable. Thus, this study is concentrated on bioethanol production and techno-economic analysis of cassava bioethanol as an alternative fuel in Malaysia. Furthermore, the current study attempts to determine the effect of bioethanol employment towards the energy scenario, environmental and economy. From the economic analysis, determined that the life cycle cost for 54 ktons cassava bioethanol production plant with a project life time of 20 years is 132 million USD, which is equivalent to 0.11 USD per litre of bioethanol. Furthermore, substituting 5 % of gasoline fuel with bioethanol fuel in road transport can reduce the CO2 emissions up to 2,038 ktons in year 2036. In case to repay the carbon debt from converting natural forest to cassava cropland, cassava bioethanol required about 5.4 years. The cassava bioethanol is much cheaper than gasoline fuel even when 20 % taxation is subjected to bioethanol at current production cost. Thus, this study serves as a guideline for further investigation and research on bioethanol production, subsidy cost and other limitation factors before the extensive application of bioethanol can be implemented in Malaysia.
Keywords: 330; Bioethanol; Environmental assessment; Sri Kanji 1 cassava; Techno-economic analysis